Perlindungan Hukum Terhadap Kurir Jika Terjadi Ketidaksesuaian Pengiriman Barang Terhadap Konsumen Dalam Transaksi Cash on Delivery (COD) - Muh Ersandi Rizki Pratama; Sutrisno Sutrisno (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
The digital world offered by the sophistication of the Internet, presents new innovations that change old conventional habits. The existence of the development of the internet, presents an innovation where the market can be reached anytime and anywhere, and under any conditions known as E-commerce or electronic commerce. The sale and purchase is considered to have occurred if both parties have agreed on the goods and prices, even though the goods have not been delivered or the price has not been paid. The formulation of the problem is regarding the legal relationship of the parties in COD transactions, as well as legal protection in COD transactions. The method used in compiling this research is a research with a normative method approach. The source of the research that the author took is in the form of normative analysis related to regulations related to the protection of couriers, such as Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, Law Number 22 of 2009 concerning Road Traffic and Transportation, and Law No. Number 38 of 2009 concerning post. The COD mechanism does not stop only at the relationship between the seller and the buyer, but involves parties that are very important for the operation, namely the delivery service company and courier delivery service, which presents a new legal relationship in the COD transaction process. Couriers in delivering goods to consumers or recipients of goods are also responsible for the goods delivered, if there is damage on the basis of negligence on the part of the courier, the courier is responsible for the goods, however, as long as it is not the fault of the courier, the courier will not be charged and compensation for damaged goods.